Analisis Usability Pada Aplikasi Mobile E-Government Layanan Aspirasi dan Pengaduan Online Rakyat (LAPOR!) Dengan Heuristic Evaluation - Tiur Prasetyaningtias; Hanifah Muslimah Az-Zahra; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
LAPOR! app is a complaint app made by Indonesian President's Staff Office. LAPOR! could be accessed by sms, mobile app and website. The research before found many usability problem on the website. Usability evaluation is important to do, the easier the e-government app the more accepted by Indonesian citizen. The first observation found a few problems about efficiency and satisfaction which is one of the usability level's factor. Evaluation is needed for LAPOR! app to find usability problems more detail. Usability evaluation uses heuristic evaluation with Nielsen's 10 principals : visibility of system status, match between system and the real world, user control and freedom, consistency and standards, error prevention, recognition rather than recall, flexibility and efficiency of use, aesthetic and minimal design, help user recognize, diagnose, and recover from errors and help and documentation. The problems categorized with severity ratin scale 0-4. Evaluation done twice. The outcome from first heuristic evaluation were 20 problems and 2 problems non heuristic. Refinement involve user interface, content and flow. The second heuristic evaluation found 8 problems. After done the refinement, a few of the first heuristic evaluation's problems not found in the second heuristic evaluation, but we found new problems.